GAMBARAN TINGKAT PENGETAHUAN DIABETES MELITUS DAN TINGKAT AKTIVITAS FISIK REMAJA DI INDONESIA : PENELITIAN MULTI CENTER - Prayogi, Norbertus Marcell; Faiza, Agyta Hanifa; Asmarani, Azizah Qayla; Yustian, Ahmad Raffi; Kumala, Aswa Arsa; Pratiwi, Savina Rifky; Shiddiq, Muhammad Rais; Khaerunisa, Hana Nadya; Ridwan, ⁠Muhammad Hanif Muthahhari; Cindy, Iffah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Background: Adolescents, as a vulnerable group, need to have a good understanding of diabetes and adopt a healthy lifestyle to prevent this disease. Objective: This study aims to analyze the level of knowledge about diabetes melitus and the level of physical activity among adolescents in Indonesia. Methods: This is a descriptive cross-sectional study involving high school students from various regions in Indonesia. Data was collected using a questionnaire to measure knowledge about diabetes and physical activity levels. Results: The results showed that most adolescents had a fair understanding of diabetes, but many still lacked adequate knowledge. The overall level of physical activity among adolescents was still low, especially among females and 18-year-olds. Discussion: The low level of physical activity and inadequate knowledge about diabetes among adolescents is a problem that needs to be addressed immediately. Factors such as gender, age, grade, and domicile can influence the level of knowledge and physical activity of adolescents. Conclusion: This study highlights the importance of improving adolescents' knowledge about diabetes and encouraging them to be more physically active. School-based interventions involving parents and utilizing digital technology can be effective solutions to achieve this goal.